TRPM channels as potential therapeutic targets against pro-inflammatory diseases. (November 2017) - Zierler, Susanna; Hampe, Sarah; Nadolni, Wiebke
Graphical abstract: Highlights: Calcium signaling cascades are essential for immune cell activation and subsequent immune responses. Melastatin-like transient receptor potential (TRPM) cation channels play crucial roles in calcium signaling. Thus, TRPM channels are essential for leukocyte physiology. TRPM channels represent potential pharmacological targets against pro-inflammatory diseases. Abstract: The immune system protects our body against foreign pathogens. However, if it overshoots or turns against itself, pro-inflammatory diseases, such as rheumatoid arthritis, inflammatory bowel disease, or diabetes develop. Ions, the most basic signaling molecules, shape intracellular signaling cascades resulting in immune cell activation and subsequent immune responses. Mutations in ion channels required for calcium signaling result in human immunodeficiencies and highlight those ion channels as valued targets for therapies against pro-inflammatory diseases. Signaling pathways regulated by melastatin-like transient receptor potential (TRPM) cation channels also play crucial roles in calcium signaling and leukocyte physiology, affecting phagocytosis, degranulation, chemokine and cytokine expression, chemotaxis and invasion, as well as lymphocyte development and proliferation. Therefore, this review discusses their regulation, possible interactions and whether they can be exploited as targets for therapeutic approaches to pro-inflammatory diseases.